Environmental sustainable intiative rainwater harvesting / Nik Muhammad Faris Nik Hassim - Nik Hassim, Nik Muhammad Faris (2014)
The purpose of this research is to identify the benefit of rainwater harvesting system. Other than that, this research also carried out to identify the problem relating to rainwater harvesting and to see whether this system is practical to be applied in order to reduced monthly cost. This research is carried out to various of case study. The area of the research location is around Selangor and Kuala Lumpur. The number of case study for this research is five building that applied this system in their building. The method of carrying out this research is by using interview. The target respondent is the competent person who handle and taking care of rainwater harvesting system. That is because to obtained the detail and accurate data from the person that had been interviewed. The conversation from interview will be recorded and it will be transcribed. Only the important data will be transcribed which related to the research.